Epilogue -- Writing in the Aftermath: Digital Humanities, c. 1600? - Mazzio, Carla (Journal of the Northern Renaissance, 2014)
The article focuses on the role of numbering in the modern world, and talks of dependence of symbolic notation, computer coding, and algorithms to analyse big data, distinction between abstract numbers and material things, and relation between digital technology and humanity.